Rate of Compliance with Crash Helmets Use by Powered Two-Wheelers in Nigeria (2011)
Head injuries remain the main cause of deaths among users of Powered Two- Wheelers (PTW). Therefore, helmet use represents the major measure for reducing the severity of head injuries. However; in most developing countries especially in Nigeria, compliance to the use of crash helmets is extremely poor: Using observational survey, the study evaluated the level of compliance of motorcycle riders to the use of crash helmets on three categories of roads in Abeokuta, Nigeria. In addition, 250 powered two-wheelers (motorcyclists) were served with 250 copies of questionnaire each using systematic sampling. Findings indicated that more than 75% of them were less than 40 years in age and about 68% had no more than secondary education. In terms of helmet wearing, 29%, 15% and 62% compliance rates were recorded on Trunk 'A' collector and access roads respectively. Also, 34.2% and 27.6% identified heat and cost of the crash helmets as main reasons for poor use of crash helmets. One Way ANOVA showed a significant difference (p<0.05) in the use of crash helmets on the three categories of roads. The paper calls for effective enforcement of crash helmet law, more enlightenment programme and the need to subsidize the cost of crash helmets in order to improve the wearing rate in the country.